Clinical Quiz—Newborn Female with an Anorectal Malformation and a Gynecological Abnormality - Apte, Anisha; Mayhew, Allison; McKenna, Elise; Gomez-Lobo, Veronica; Levitt, Marc A. (European Journal of Pediatric Surgery Reports, 2022)
We present a case of a newborn female with imperforate anus who on exam was found to have a rectal fistula in the vestibule, no vaginal opening, and a normal urethra. A diagnostic laparoscopy was performed to elucidate the internal anatomy. The case is presented with a focus on surgical strategies in approaching the female patient with anorectal malformation and a Mullerian anomaly, with questions for the readers posed in a quiz format.
Keywords: anorectal malformation; imperforate anus; Mullerian anomalies; vestibular fistula; vaginal atresia